1999
DOI: 10.1097/00006454-199911000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Renal candidiasis in neonates with candiduria

Abstract: Serial renal ultrasounds are required to reliably detect late appearing renal fungus balls in neonates with candiduria. Complications requiring surgical intervention, like urinary tract obstruction, were uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 21 publications
2
46
0
3
Order By: Relevance
“…This may reflect a lack of consensus on the need for obtaining this ancillary test as well as the definition of a ''positive'' finding. Previous reports demonstrated a 42% incidence of renal fungal involvement in a population of 41 infants with candiduria, 17 but other series have reported the incidence of abnormal RUS findings to be more consistent with our own at 4.6% 23 and 7.1%. 7 Irrespective of the incidence of fungal infiltration in the kidney, the therapeutic dilemma posed by abnormal RUS findings in the setting of normal renal function and negative repeat cultures remains.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This may reflect a lack of consensus on the need for obtaining this ancillary test as well as the definition of a ''positive'' finding. Previous reports demonstrated a 42% incidence of renal fungal involvement in a population of 41 infants with candiduria, 17 but other series have reported the incidence of abnormal RUS findings to be more consistent with our own at 4.6% 23 and 7.1%. 7 Irrespective of the incidence of fungal infiltration in the kidney, the therapeutic dilemma posed by abnormal RUS findings in the setting of normal renal function and negative repeat cultures remains.…”
Section: Discussionsupporting
confidence: 90%
“…This finding suggests that serial brain imaging may be valuable in cases of persistent candidemia, as others have described for RUS imaging. 17,31 Ophthalmologic involvement in neonates with candidemia has been reported in 0% 7,24 to 6% 23 of patients who underwent examinations. These cases demonstrate the importance of ophthalmologic examination in neonatal candidiasis, but currently available data are restricted primarily to clinical series, thus firm recommendations regarding timing of the examination cannot be made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the frequency of candiduria was higher among children than adults (62% vs 25.4%, P = 0.001) (Table 1). Bryant et al (1999) (32) upon conducting a 12-year study in the large tertiary care neonatal ICUs in the USA, established the overall incidence of candiduria to be 0.5%. In contrast, another study in the USA (33) demonstrated a greater prevalence of Candida species causing UTI in 42% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…When a Candidal urinary tract infection (UTI) is diagnosed in a neonate, it is important to assess the patient for candidemia. Phillips and Karlowicz found candidemia in 13 of 25 Candidal UTIs in neonates and Bryant et al reported this condition in 12 of 36 cases (7,8). Renal involvement in neonatal candidemia varies from 5% to 33% (9-11).…”
Section: Urinary Tract Infection With Candidamentioning
confidence: 99%